2020
DOI: 10.1101/2020.09.26.314724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of a newNeisseria gonorrhoeaeType IV pilus assembly factor, TfpC

Abstract: Neisseria gonorrhoeae rely on Type IV pili (T4p) to promote colonization of their human host and to cause the sexually transmitted infection, gonorrhea. This organelle cycles through a process of extension and retraction back into the bacterial cell. Through a genetic screen, we identified the NGO0783 locus of N. gonorrhoeae strain FA1090 as containing a gene encoding a protein required to stabilize the Type IV pilus in its extended, non-retracted conformation. We have named the gene tfpC and the protein TfpC.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…TfpC, which was only recently identified as a new type IV pilus biogenesis factor, is located in the periplasm and harbours an N-terminal transmembrane domain anchoring the protein to the inner membrane. Deletion of tfpC resulted in nonpiliated colony morphology and reduced transformation competence and it was hypothesized that TfpC stabilizes the pilus in its extended conformation [52]. mRNA quantification indicated that NGFG_01479, encoding the minor pilin PilV [72], is controlled by TfpR1 as well (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TfpC, which was only recently identified as a new type IV pilus biogenesis factor, is located in the periplasm and harbours an N-terminal transmembrane domain anchoring the protein to the inner membrane. Deletion of tfpC resulted in nonpiliated colony morphology and reduced transformation competence and it was hypothesized that TfpC stabilizes the pilus in its extended conformation [52]. mRNA quantification indicated that NGFG_01479, encoding the minor pilin PilV [72], is controlled by TfpR1 as well (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For initial validation experiments, hits showing complementarity between the predicted sRNA single stranded region and the mRNA region comprising RBS and start codon were taken into consideration (Tables S3 and S4). NGFG_01006 encoding the type IV pilus biogenesis factor TfpC [52] and NGFG_00693 encoding an aminotransferase were the only hits meeting these criteria which scored in the outcome of both in silico target prediction tools. However, no significant differences in the transcript amounts of tfpC and NGFG_00693 were observed in qRT-PCR experiments performed on RNA extracted from MS11 wild-type and the sRNA deletion mutant MS11 ΔtfpR1.…”
Section: Identification Of Putative Tfpr1 Target Genesmentioning
confidence: 99%
See 1 more Smart Citation